Corps perdu d’Aimé Césaire et de Pablo Picasso, un recueil de guerres et de paix - Kora Véron (Continents manuscrits)
On June 1950, a magnificent book, Corps perdu, with a print run of 220 copies, was published by Éditions Fragrance. On the cover, Aimé Césaire’s name appears at the top, but underneath, Pablo Picasso’s is much larger. How did the two men come to publish this collection? How did they develop their joint work? Corps perdu is the result of a tumultuous history.